Sports governance, development and corporate responsibility - Segaert, Barbara (New York : Routledge, 2012)
"The call for sport organizations and organizers to take up social responsibilities is reflected in a wide variety of sport-related practices. This book critically examines sport-related social interventions in different cultural settings, such as promoting local community-building by sport. Social constructions of peace, integration and managing diversity are studied from the perspective of sport and play, and the power position of global sport organizations with corporate features is discussed from the perspectives of good governance, legal issues and fair trade. Referring to Foucaults concept of biopolitics, this book contributes to the discussion on the rising power position and the social responsibilities of sports and sport organizations. It is a valuable contribution to the understanding of interconnections between sport and society for students in sociology, policy and politics of sport, for sport leaders, and for policy and decision-makers in sport"--
pt. I. Building communities and social responsibility-- rising stakes on sport's social role -- pt. II. Sports corporations at play : doing business in sports-- who's added value?
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sports administration; Sports -- Management; Sports -- Social aspects; Sports and state; Electronic books